2001
DOI: 10.1191/096032701673031525
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of taurine against thioacetamide hepatotoxicity of rats

Abstract: Thioacetamide (TAA) administration (three consecutive intraperitoneal injections of 400 mg/kg at 24-h interval) to rats resulted in hepatic injury as assessed by the measurement of serum transaminase activities and histopathological findings. This treatment caused an increase in the levels of malondialdehyde (MDA), diene conjugates (DCs) and glutathione (GSH) and the activity ofsuperoxide dismutase (SOD), and a decrease in the levels of vitamins E and C and the activity of glutathione peroxidase (GSH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
45
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 24 publications
9
45
1
Order By: Relevance
“…I/R disturbs oxygen-derived free radical metabolism and induces lipid peroxidation injury, which is considered to be the most important mechanism of I/R injury pathogenesis [2] . Recently, more attention has been paid to the application of free radical scavengers and cytoprotective agents [3,4] . Taurine (2-aminoethane sulfonic acid), a sulfur-containing amino acid derived from the metabolism of methionine, is the most abundant intracellular amino acid in humans and is implicated in numerous biological and physiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…I/R disturbs oxygen-derived free radical metabolism and induces lipid peroxidation injury, which is considered to be the most important mechanism of I/R injury pathogenesis [2] . Recently, more attention has been paid to the application of free radical scavengers and cytoprotective agents [3,4] . Taurine (2-aminoethane sulfonic acid), a sulfur-containing amino acid derived from the metabolism of methionine, is the most abundant intracellular amino acid in humans and is implicated in numerous biological and physiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore possible that another mechanism besides the improving eŠect on the serum lipoprotein level may play an important role in the decreasing or preventive eŠect of taurine on atherosclerosis. In our previous studies, we have demonstrated that a taurine treatment had a protective eŠect against thioacetamide-induced hepatic necrosis 6) and cirrhosis 7) by decreasing oxidative stress. Clinical and experimental studies have shown that oxidative stress and lipid peroxidation are involved in the pathogenesis of atherosclerosis.…”
mentioning
confidence: 95%
“…Moreover, hypotaurine, an intermediate in the biosynthesis of taurine, has been reported to scavenge free radicals in vivo (13). There are several reports on the protective effects of taurine against hepatotoxicity induced by chemicals (14,15) or xenobiotics (16,17). Its protective effects seem to extend to other types of cells as well (18,19), and have even been reported in clinical settings against diabetes (20) and pancreatitis (21).…”
mentioning
confidence: 99%